CARTOGRAPHY OF THE SOCIOECONOMIC AND HOUSING PROFILE IN THE MICRO-BASIN OF THE RÍO BURÍO QUEBRADA SECA (COSTA RICA) - Masís-Campos, Ramón (2020)
The main objective of the research is to map the socioeconomic and housing profile in the Burío-Quebrada Seca micro-basin in order to favor the implementation of restoration, conservation, mitigation actions in the fluvial system and territorial ordering in the study area. The methodology was composed of three main stages: description of data, preparation of data in the database manager, and publication of data with the community. The studied micro-basin, is mostly occupied by the Belén canton, where important avenues have been reported during the last three decades (1981, 2004, 2007, 2008) that have significantly affected the resident population, mainly with damage to dwellings and bridges. In parallel, since 2005, the Constitutional Chamber issued the vote No. 4050, in which it ordered the formation of an Inter-Institutional Commission. In terms of population density, the micro-basin for 2011 had an average of 4160 inhabitants per km². There is a predominance of urban residences in the micro watershed, 97.5% of the dwellings are in this area. Almost 87% of the homes in the study area correspond to independent houses. According to the 2011 census, for the study area, approximately 190 households do not have sanitary sewage or septic tank, distributed in 82 UGM. That is, the black and residual waters are disposed directly to rivers, ravines, trenches or hollows.  In the low micro-basin it presents a considerable amount of events in the sector San Antonio of Belén, sector that is characterized to present greater areas in the category of high threat by flood.